Achievement motivation as correlates of interest in schooling among secondary- school students in Ilorin Metropolis - Kaothar Bukola, Abdulmajeed; Esere, Mary O. (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
This study examined achievement motivation as correlates of interest in schooling of secondary school students in Ilorin metropolis. Descriptive design with correlational approach was adopted. 380 students from secondary schools in Ilorin metropolis were the participants of this study. Instrument for data collection was adapted but well validated questionnaire. Three null hypotheses were generated and tested at .05 alpha levels. Pearson Product Moment Correlation and Multiple Regression Analysis were used. Result showed a significant relationship between achievement motivation and interest in schooling of secondary school students in Ilorin metropolis (r. calculated = 0.62, df = 378 and p < 0, 05), Achievement motivation jointly contributed 82% to the variance in the interest in schooling of the participant and this is found to be significant (AR2 = 82%, F. ratio 2/377 = 854.44 and p <0.05) and that interest in schooling had the greater relative contribution to (β = 0.72) and achievement motivation also had significant relative contribution to the prediction of interest in schooling of the participants (β = 0.33). Recommendations were made based on the outcome of the study.